2007
DOI: 10.1128/aem.00048-07
|View full text |Cite
|
Sign up to set email alerts
|

Novel Nickel Resistance Genes from the Rhizosphere Metagenome of Plants Adapted to Acid Mine Drainage

Abstract: Metal resistance determinants have traditionally been found in cultivated bacteria. To search for genes involved in nickel resistance, we analyzed the bacterial community of the rhizosphere of Erica andevalensis, an endemic heather which grows at the banks of the Tinto River, a naturally metal-enriched and extremely acidic environment in southwestern Spain. 16S rRNA gene sequence analysis of rhizosphere DNA revealed the presence of members of five phylogenetic groups of Bacteria and the two main groups of Arch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(81 citation statements)
references
References 58 publications
(57 reference statements)
2
75
0
4
Order By: Relevance
“…Among them were members of the archaeal phylum Crenarchaeota, including clones from Origin sites 1 and 2 (OR1, OR2) related to sequences derived from an acidmine drainage study from the Chinese Tong ShanKou mine (96% similar to DQ901270). These were phylogenetically distinct from the crenarchaeal clones found in an RT rhizosphere study (Mirete et al, 2007) that branched among the South African gold mine crenarchaeal group-1. We further detected a singleton crenarchaeal clone from Berrocal site 2 (BE2) related to an archaeal sequence from a subsurface acid-mine drainage system (99% similar to AY082452).…”
Section: Resultsmentioning
confidence: 61%
“…Among them were members of the archaeal phylum Crenarchaeota, including clones from Origin sites 1 and 2 (OR1, OR2) related to sequences derived from an acidmine drainage study from the Chinese Tong ShanKou mine (96% similar to DQ901270). These were phylogenetically distinct from the crenarchaeal clones found in an RT rhizosphere study (Mirete et al, 2007) that branched among the South African gold mine crenarchaeal group-1. We further detected a singleton crenarchaeal clone from Berrocal site 2 (BE2) related to an archaeal sequence from a subsurface acid-mine drainage system (99% similar to AY082452).…”
Section: Resultsmentioning
confidence: 61%
“…The other newly detected bacterial indicators of metal contamination identified here are Planctomyceteceae DQ906072 and Xanthomonadales FJ228294. The clone sequences of accession numbers DQ906072 and FJ228294 originate from the rhizosphere of plants adapted to acid mine drainage (50) and acidic mine pit lakes (www.ncbi.nlm.hih.gov), respectively. This supports our results, implying the presence of two unknown bacterial species that predominantly inhabit metal-contaminated acidic soils.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent metagenomic analysis of the rhizosphere of plants growing in the banks of Rio Tinto (Mirete et al 2007), new genetic systems conferring nickel resistance have been identified by screening an E. coli library: these include ABC transporters and enzymes, as serine acetyltransferase (SAT), which are known to play similar roles in hyperaccumulating plants (Freeman et al 2004). From these data an emerging hypothesis is that for bacteria several independent mechanisms may operate to confer metal resistance, emphasizing the role of the species' (and community's) gene pool and horizontal gene transfer other than that of single genes.…”
Section: Genes For Metal Resistance: Single Operons or Genome Adaptatmentioning
confidence: 99%